Semi Otomatisasi Untuk Efisiensi Tenaga Operator Pada Produk Regulator - Zazam Dumadi; Antonius Suhartomo (President University, 2018)
The purpose of this study is to explain about automation as which is one step to reduce costs due to rising wages of employees every year. The other purpose of machine automation is to improve product quality. This project was carried out at PT. XYZ which produces automotive parts, one of which is a regulator product that functions as a voltage stabilizer on the car charge dynamo. This automation uses 2 methods, namely the method of dividing the operator's total work and machine improvisation. The machine that is automated in the Regulator product is an IC Silicone Potting Regulator machine. This machine functions as a filler for silicone material and also a vacuum process. In the process of filling silicone material initially using operator assistance. The target of this automation is to replace the role of the operator to fill the silicone material and be replaced by the machine. As a component of the automation of this machine, the author uses the IAI ROBO Slider. Where IAI ROBO Slider is able to move in certain positions as desired. This automation study also confirms or checks product quality so that product quality is maintained before and after the engine automation project. The results of this automation are able to reduce 1 operator in the regulator product, so as to reduce the operator's overall working hours each month. This automation project was obtained by Break Event Point (BEP) for 2.35 months. Keywords: Automation, machine IC Silicone Potting Regulator, operator, silicone material, IAI ROBO Slider, Break Event Point.